2011
DOI: 10.1007/s10661-011-2428-5
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality assessment in child care and medical facilities in Korea

Abstract: In order to characterize the status of indoor air pollution in some important facilities, a list of key criteria pollutants [particulate matter (PM(10)), carbon dioxide (CO(2)), carbon monoxide (CO), formaldehyde (HCHO), and bioaerosol] was measured from a total of 91 randomly selected sites in 18 different cities, Korea (February 2006 to December 2009). The target facilities include 43 child care facilities, 38 medical facilities, 6 elementary schools, and 4 postnatal care centers. The results showed that som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
2
22
1
Order By: Relevance
“…These effects are often related to changes in ventilation and air exchange patterns dependent on seasonal changes [6,25]. We do not expect that season has much influence on the results of our study because of centralized air treatment and conditioning and the absence of facilities for natural ventilation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These effects are often related to changes in ventilation and air exchange patterns dependent on seasonal changes [6,25]. We do not expect that season has much influence on the results of our study because of centralized air treatment and conditioning and the absence of facilities for natural ventilation.…”
Section: Discussionmentioning
confidence: 91%
“…As shown in Table S6, in our study, naphthalene was confirmed at the source but not detected in the ORs before or during/after starting the power supply engines. Most of these substances have known indoor sources and were previously reported in indoor hospital environments [6,20,21,22,25]. However, naphthalene is a gas-phase constituent of combustion processes not likely found in an indoor environment devoid of open fire or other combustion source.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of the studies used passive samplers for the exposure of interest, which have been found to underestimate the levels of weak sorbents such as benzene [ 69 ]. Furthermore, previous studies failed to assess seasonal trends which are known to act as an important factor for IAP levels with higher winter levels for PM and CO 2 and exhibited higher concentration in warmer seasons for formaldehyde and bioaerosol [ 70 , 71 ]. Moreover, existing studies failed to take into consideration other important factors including ventilation, cleaning condition, cultural habits, outdoor pollution and climate which may alter indoor levels of exposure [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…IAQ is a significant problem in the healthcare sector where air quality is likely to be a major risk factor for both staff and patients who visit the facility (Krajewska et al [20]). There are various pollutants in buildings which include CO2, CO, NO2, O3, HCHO, TVOC, respirable suspended particulates, radon and bacteria (Kabir et al [19] and [28]). These can adversely affect our health ranging from the sick building syndrome to Building Related Illnesses (BRI) such as pneumonitis and cancer at various degrees of severity.…”
Section: 2mentioning
confidence: 99%